Correlation between differentiation grade and lymphovascular invasion in colorectal adenocarcinoma - Nana Liana; Loli Devianti; Yessy Setiawati; Sri Nani Jelmila; Ruhsyahadati (Published by Universitas Gadjah Mada, 2025)
Colorectal carcinoma is the third most common malignant tumor worldwide. It is a heterogeneous disease with diverse clinicopathological and prognostic characteristics. The TNM (tumor, node, metastasis) staging system is currently used as a prognostic predictor. However, its predictive value is limited, as approximately 30% of patients with lymph node-negative disease die due to metastasis progression. It is suspected that other prognostic factors other than TNM staging system, may play a significant role. Differentiation grade and lymphovascular invasion have been proposed as essential prognostic factors for lymph node-negative colorectal carcinoma. This study aimed to evaluate the correlation between differentiation grade and lymphovascular invasion in colorectal carcinoma. It was an observational study with a cross-sectional design. Samples were collected from 4 Anatomical Pathology laboratories in West Sumatera in 2018. A total of 97 paraffin blocks of colorectal adenocarcinoma met the inclusion criteria. Differentiation grade and lymphovascular invasion were evaluated according to the 2019 World Health Organization (WHO) classification. The correlation between differentiation grade and lymphovascular invasion was analyzed using Fisher's Exact test. A p value <0.05 considered statistically significant. The most prevalent age group for cases of colorectal adenocarcinoma was 51–60 yr (36.1%). Low-grade differentiation was the most common grade of differentiation (72.2%). Lymphovascular invasion in small vessels was commonly encountered (73.3%). High-grade differentiation adenocarcinomas had 100% lymphovascular invasion. A significant correlation between differentiation grade and lymphovascular invasion was observed (p = 0.031). This study confirms that lymphovascular invasion is a valuable predictor of colorectal carcinoma progressiveness.